Effector Cells and Downstream Mediators in Severe Cutaneous Adverse Reactions - Bellon, Teresa (Current Immunology Reviews (Discontinued), 2014)
Cutaneous adverse drug reactions are unpredictable and represent a plethora of skin diseases of varying degrees of severity. Those of most concern are usually referred to as severe cutaneous adverse reactions (SCARs), and include acute generalized exanthematous pustulosis (AGEP), drug reaction with eosinophilia and systemic symptoms (DRESS), also known as drug-induced hypersensitivity syndrome or hypersensitivity syndrome (DIHS/HSS), Stevens-Johnson’s syndrome (SJS), and toxic epidermal necrolysis (TEN). All are delayed type IV hypersensitivity reactions in which a T cell-mediated drug-specific immune response is responsible for triggering the disease. Nonetheless, specific T cell subpopulations develop in response to certain environments and produce cytokines that orchestrate the various phenotypes. Tc1, Th1, Th2, Th17, and Treg, among other T cell subpopulations, participate in several SCARs. Immune cells belonging to the classically known as the innate immune system, comprising natural killer cells, monocytes, macrophages and dendritic cells, can also participate in shaping specific immune responses in various clinical entities. Additionally, tissue resident cells including keratinocytes can contribute to epidermal damage by secreting chemokines that attract proinflammatory immunocytes. The final phenotypes in each clinical entity result from the interactions between the cell types and their products. Although the pathophysiology of these reactions is not fully understood, intensive research during the last decade has led to major progress in our understanding of the contribution of certain cell types to the variability of SCAR phenotypes.
Keywords: drug hypersensitivity